2008
DOI: 10.1017/s0022112008003091
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of physical mechanisms in the control of supersonic impinging jets using microjets

Abstract: Supersonic impinging jet(s) inherently produce a highly unsteady flow field. The occurrence of such flows leads to many adverse effects for short take-off and vertical landing (STOVL) aircraft such as: a significant increase in the noise level, very high unsteady loads on nearby structures and an appreciable loss in lift during hover. In prior studies, we have demonstrated that arrays of microjets, appropriately placed near the nozzle exit, effectively disrupt the feedback loop inherent in impinging jet flows.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 37 publications
6
23
0
Order By: Relevance
“…A recent approach to suppress the feedback mechanism of supersonic impinging jets using an array of high-momentum microjets appropriately placed near the nozzle exit has shown highly promising results [15][16][17][18][19]. This control-on-demand technique has many advantages over traditional passive and active control methods and has proven to be successful over a range of geometric and flow conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent approach to suppress the feedback mechanism of supersonic impinging jets using an array of high-momentum microjets appropriately placed near the nozzle exit has shown highly promising results [15][16][17][18][19]. This control-on-demand technique has many advantages over traditional passive and active control methods and has proven to be successful over a range of geometric and flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This control-on-demand technique has many advantages over traditional passive and active control methods and has proven to be successful over a range of geometric and flow conditions. With the help of particle image velocimetry (PIV) measurements, Alvi et al [19] have shown that one of the main mechanisms at work is the introduction of streamwise vorticity at the expense of azimuthal vorticity of the main jet. A reduction in the primary shear-layer instability, attenuation of upstream propagating acoustic waves, and disruption of spatial coherence between largescale structures and the acoustic field lead to an overall attenuation in the feedback loop.…”
Section: Introductionmentioning
confidence: 99%
“…Both acoustic and PIV measurements were conducted on control of a Mach 1.5 ideally expanded free and impinging jets using an array of circumferentially placed 16 steady MJs 400 μm in diameter and with injection angles of 60 • [57]. The combined mass flow from the MJ configuration is only 0.5 % of the main jets [58,59]. The velocity field measurements indicate that the MJs result in a rapid nonlinear thickening of the shear-layer growth, particularly near the nozzle exit, as opposed to the uncontrolled case.…”
Section: Thematic Issue On Supersonic Flow Controlmentioning
confidence: 99%
“…Mahesh [4] provides a recent, comprehensive review of single jets in crossflow. Some applications of jet injection include fuel injectors in scramjets [5][6], active flow control of cavities in supersonic flow using micro-orifice jets [7][8], suppression of jet noise in high-speed flows among others (Alvi et al [9]). Interaction of the injectant with the supersonic crossflow creates a shock wave, where a sufficiently strong shock wave (due to high injection pressures or momentum flux) is capable of separating the incoming boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…The cross-stream velocity (V/U o ) contours show significant negative velocities with a magnitude of -0.09 near jet exit, and close to the edge of the boundary layer (0.1H), which is an indication of the strong penetration of the microjets into the crossflow. The significant penetration of the injectant into the freestream results in generating streamwise vorticity (see Alvi et al [9]; Mahesh [4]; Fernandez et al [23]) and leads to higher mixing with the freestream flow. This feature was exploited in another study where microjet arrays are used as mixing enhancement actuators upstream of a backward facing step in a supersonic flow (Ahmed et al [24]).…”
mentioning
confidence: 99%